O êxtase como elemento narrativo na construção de personagens de Hilton Lacerda : uma análise do filme Tatuagem - Aragão, Isaac Dourado (2018)
This dissertation invites to an analysis about the manifestation of ecstasy as main narrative element in the construction of characters written by the screenwriter and director Hilton Lacerda, specially in the movie Tattoo (2013). Such analysis comes interspersed of the following reflections: How and when happens any kind of extactic manifestation – and this phenomenon’s complexity – the fictional characters appreciated in a movie so impregnated of realism? What can they establish? Is there any strangeness and distancing of themselves? In order to answer these inquiries, it will be required to know the filmic path created by the abovementioned filmmaker by the way of the characters’ development, as representations of narrative processes in which the experience of ecstasy defines subjectivities marked, ethics and aesthetically, by a notion of freedom. In the search for this understanding, it will be necessary to investigate some cultural references which are part of the director’s influence lines’construction, regarding his filmic work and thought. Therefore, we will divide our reflections in three integrated parts that will establish the core of our thought. In the first part, called From the reception to the filmic analysis: the characters and the ecstasy we seek to do a decoupage of Tattoo, to contextualise the way how the ecstasy and subjectivity flow between his characters, and how his narrative process has the power of handling the particularities of each one. In it, we will also see how other characters written by Hilton Lacerda present themselves in a memorable way with regard to ecstasy, and how, from this phenomenological element, they map their lives. The second part, under the title Theoretical-methodological definition of the character’s notion, subjectivity and ecstasy, will consist in analysis’ construction with an explanation of specific scenes, followed by a theoretical reflection about ecstasy, character and realism, through a theoretical framework of philosophical, theological and literary studies, as well as cinematographic theory. In this regard, we will meditate in a interdisciplinary way on some aesthetic-realistic aspects vibrantly present in Lacerda’s work, which main reference was transferred from the livingness of a political, historical, social and cultural brazilian context. On the third and last approach, Tattoo: an analysis of Hilton Lacerda’s movie under the standpoint of ecstasy as a narrative/dramatic situation key of characters’ construction, we will verify how the walk of each one of them to the revelation and ecstasy is configurated through the compositional universe of the director’s narrative, as well as the reflexes that the protagonists’ parallels and suspensions provoked in the plot. Truly, the movie is the theoretical text that we try, here, to decipher.